2018
DOI: 10.1093/beheco/ary009
|View full text |Cite
|
Sign up to set email alerts
|

A marker of biological ageing predicts adult risk preference in European starlings, Sturnus vulgaris

Abstract: Why do some individuals gamble more than others? Existing theories, based on how close animals are to starvation, have been only weakly supported by evidence. We found that faster ageing birds were less likely to gamble while foraging. We measured biological ageing in starlings from the shortening of DNA sequences called telomeres. Birds’ whose telomeres shortened more had stronger preferences for a foraging option yielding a consistent amount of food over a variable amount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
1
13
1
Order By: Relevance
“…Both groups increased dawn body masses over time, which is potentially due to both groups being subjected to an environment with unpredictable food availability. We are unable to definitively say that the increase in body mass was due to a variable food supply as no control group (with no food deprivation) was present; however, in another experiment of similar duration where the food supply was kept constant (Andrews et al, 2018), we found that the rate of weight gain in long-term individually caged starlings was only 66% of that reported here. Thus, our results align with previous studies on starlings (Cuthill et al, 2000;Witter et al, 1995) and great tits, Parus major (Bednekoff & Krebs, 1995), which increased their weight in response to an unpredictable food environment.…”
Section: Discussioncontrasting
confidence: 83%
“…Both groups increased dawn body masses over time, which is potentially due to both groups being subjected to an environment with unpredictable food availability. We are unable to definitively say that the increase in body mass was due to a variable food supply as no control group (with no food deprivation) was present; however, in another experiment of similar duration where the food supply was kept constant (Andrews et al, 2018), we found that the rate of weight gain in long-term individually caged starlings was only 66% of that reported here. Thus, our results align with previous studies on starlings (Cuthill et al, 2000;Witter et al, 1995) and great tits, Parus major (Bednekoff & Krebs, 1995), which increased their weight in response to an unpredictable food environment.…”
Section: Discussioncontrasting
confidence: 83%
“…Birds with greater developmental telomere attrition (those that reacted the most to the high-competition treatment) had a stronger preference for smaller but more immediate food rewards than birds with less developmental attrition or longer telomeres. A subsequent study from the same team found that biological aging in starlings is associated with higher levels of risk aversion (Andrews et al 2018). Baumard: Psychological origins of the Industrial Revolution Bateson et al's experiment perfectly illustrates the potential of adaptive plasticity and LHT, in particular, to help us understand historical changes.…”
Section: The Mechanism Of Adaptive Plasticitymentioning
confidence: 98%
“…However, there is an ongoing debate about the conditions that favor innovativeness, with seemingly conflicting evidence: some findings show that necessity (scarcity) boosts innovation, whereas others, as highlighted by Baumard, support the notion that opportunity (affluence) is the mother of invention (e.g., Benson-Amram & Holekamp 2012;Bokony et al 2013;Keynan 2016;Laland & Reader 1999;Morand-Ferron et al 2011;Sol et al 2012;Thornton & Samson 2012). Thus, Baumard presents research that identifies increased exploration and innovativeness in less-stressed individuals (Andrews et al 2018;Bateson et al 2015). In contrast, the necessity drives innovation hypothesis (Bokony et al 2013;Boserup 1965;Laland & Reader 1999;Reader & Laland 2003;Thornton & Samson 2012) suggests that risk-taking, explorative, and innovative behaviors are to be expected in stressed and subordinate individuals with less access to resources, because it is those individuals that must be creative to increase their fitness (Berger-Tal et al 2014;Houston & McNamara 1999;Kolodny & Stern 2017;McNamara & Houston 1992).…”
Section: Are Both Necessity and Opportunity The Mothers Of Innovations?mentioning
confidence: 99%